CONSTIPATION CURE AND TREATMENT THROUGH DIET, YOGA, HOME REMEDIES - Sushant Sukumar, Bargale; Shashirekha, HK (International Journal of Ayurveda and Pharma Research, 2015)
Constipation is a common disturbance of the digestive system where the difficulty during defecation or the sensation of incomplete bowel evacuation. Bowel frequency is influenced by several factors including intake of dietary fiber, emotional make up, and psychological morbidity. Introspective individuals have a lower bowel frequency and produce less stool than extroverts. Infrequent bowel actions in the absence of symptoms can be regarded as part of the normal spectrum of bowel frequency. Low bowel frequency is more common in women. Constipation is a common problem of elderly people of age 60 plus where use of laxative is frequent. Constipation is supposed to be the main cause of all diseases. Therefore, it should be treated thoroughly. Several other diseases and disorders also crop up if the bowel is constipated. Constipation can cure easy by practicing some Yogasana (postures) Bhujanghasana, Trikonasana (triangular stretch pose), Ardha Matsyendrasana (Half spinal twist), Supta Vajrasana (the sleeping pelvic pose), Dhanurasana (Bow pose), Sarvangasana (Shoulder stand) and Kapalabhati (frontal brain bellowing), Pranayama. The most important cause of constipation is diet with low dietary fiber and heavy fat. Diet which contains high fiber leads to overcome constipation more powerfully.